Potret Pembelajaran Sejarah Berbasis Kurikulum Merdeka di SMA Negeri 1 Banyuwangi - Alisa Febiyanti; I Kadek Yudiana; Riztika Widyasari (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The independent curriculum is one of the curriculum concepts that demands learner independence. The independent curriculum is closely related to constructivism learning theory which involves student participation in the learning process. In the sense that students are invited to find answers to the questions posed, the application of projects shows the teacher's efforts to create conducive learning. The purpose of this research is to find out how the portrait of history learning based on the independent curriculum starts from planning, implementation, evaluation, and obstacles in learning history at SMA Negeri 1 Banyuwagi. The method used in this research is descriptive method with qualitative approach and case study research type. The research subjects are the principal, deputy head of curriculum, history teacher, and students. The data collection techniques to be used are observation, interview and documentation study. Data were analyzed by reducing data, presenting data, and drawing conclusions. The results show that history learning in the independent curriculum includes learning planning such as making teaching modules, implementing learning and evaluating learning which consists of formative and summative assessments.